In vitro study of antimicrobial and cell viability on newly synthesized bioglass-based bone grafts: Effects of selenium and silver additions - Aksakal, B.; Demirel, M. (SAGE PUBLICATIONS LTD, 2018)
Selenium (Se)- and Silver (Ag)-doped Bioglass((R))-based biografts were synthesized using the sol-gel method. Fourier-transform infrared spectroscopy, inductively coupled plasma mass spectrometry, scanning electron microscopy and energy-dispersive X-ray analyses were carried out in order to examine mechanostructure of synthesized bioglass-based bioceramics. The effects of Se and Ag additions on cell viability were investigated via cytotoxicity and antibacterial activity analysis, respectively. The bacteria of Escherichia coli (E. coli, JM103) and Gram-positive Staphylococcus aureus (S. aureus, ATCC29293) were used to perform the antibacterial tests. Moreover, cell viability studies were conducted using the Saos-2 osteoblast cells by performing dimethylthiazol diphenyltetrazolium bromide assay. It was observed that while (PO4)(3-) and (CO3)(2-) peaks were observed in Fourier-transform infrared spectroscopy analyses, crystallinity also increased with increasing amount of AgNO3 addition into the Bioglass((R)). In addition, it was determined from scanning electron microscopy images that small irregular thin lamellar grain distribution was formed in synthesized B45Ag5Se20 and B30Ag10Se15 biografts. From antibacterial activity tests, it was determined that while some grafts was affected by E. coli, which is a Gram-negative, however, some did not affect the Gram-positive S. aureus and had antimicrobial activity on E. coli and S. aureus. According to the cell viability tests, it was found that the synthesized grafts did not have toxic effect on living cells. While the cell growth was greater for some grafts, however, some others had lower growth.
Keywords: Bioglass; selenium; silver; antimicrobial; cell viability; bone grafts; BIOACTIVE GLASS SCAFFOLDS; VIVO; NANOPARTICLES; INFECTIONS; PROTECTION; TOXICITY; SURFACES; COATINGS; APATITE; GROWTH; Engineering